EFFECT OF FAMILY EMPOWERMENT IN ENHANCING THE CAPABILITIES OF CHILDREN WITH AUTISM - Suprajitno Suprajitno (Belitung Nursing Journal, 2017)
Background: Children with autism as individuals have a right to receive developmental needs obtained from parent/caregiver during their stay in the family. The family ability can be improved through empowerment training to provide stimulation for the development of children with autism. Objective: This study aims examine the effect of family empowerment in enhancing the capabilities of children with autism. Methods: The research design used a two-stage quasi-experiment. The first stage was a training for parent/caregiver of children with autism using modules. Training was done three times in the Autism Service Center (PLA) of Blitar City Indonesia. The second stage was the parent/caregiver provided stimulation to their children at home. There were 33 children selected using total sampling in the PLA of Blitar City on April – August, 2016. Data were analyzed using descriptive statistics and paired t-test. Results: The family ability to stimulate the capability of children with autism in the sense of hearing, vision, motoric, and inviting to play obtained average changes of 61.99%, with average items increased from 18.52 to 30.00. While the increase capabilities of children with autism were categorized into five classification: communication, fulfilling of activity daily living, language-numbers–tactile, psychology, and understanding commands. Conclusion: There was a significant effect of family empowerment in enhancing the capabilities of children with autism. Thus, training to improve the ability of parent/caregiver in caring children with autism needs to be implemented in a planned and gradually manner.